Personality as a text forming category (texts of various functional styles) - M.Yu.Zakarova, M.N. Levchenko, I.V.Elistratova, (Opción, 2019)
The purpose of research is to describe the general, particular and invariant characteristics of personal architectonics of texts of artistic, official-business, scientific and journalistic styles. On the basis of the conducted segment analysis of the text it is established that the category of personality helps the textto form a specific form of narrative.At comparing texts in Russian, German and English, the authors prove that their grammatical differences have a number of features associated primarily with the linguistic specificity of the personal system of each language, as well as with the pragmatic task of each particular text.